A novel mitigator of enzymatic browning—hawthorn leaf extract and its application in the preservation of fresh-cut potatoes. (9th June 2021) - Qiao, Liping; Wang, Hailin; Shao, Jinsheng; Lu, Laifeng; Tian, Jinhu; Liu, Xia
Abstract: Objectives: The purpose of this study was to evaluate the antibrowning functions of hawthorn leaf extract on fresh-cut potato and its possible mechanism. Materials and Methods: Fresh-cut potatoes were treated with different concentrations (0.01%, 0.05%, and 0.1%) of hawthorn leaf extract and preserved at 4 ℃ for 8 days. The appearance and colour of potato slices were evaluated, along with the content of the phenol, malondialdehyde (MDA), and hydrogen peroxide (H2 O2 ) during cold storage. Meanwhile, the activities of polyphenol oxidase (PPO), peroxidase (POD), phenylalanine ammonia-lyase (PAL), lipoxygenase (LOX), catalase (CAT), superoxide dismutase (SOD), and the antioxidant capacity were determined. Furthermore, the composition of hawthorn leaf extract was analyzed by high-performance liquid chromatography–tandem mass spectrometry (HPLC-MS/MS). Results: The addition of hawthorn leaf extract effectively delayed the browning process. It not only enhanced the CAT activity and antioxidant capacity but also reduced the LOX activity and accumulation of MDA and H2 O2 . Meanwhile, the activities of PPO, POD, and PAL as well as the content of phenol were controlled. Additionally, 25 phenols, 34 flavonoids, and 5 proanthocyanidins were identified through high-performance liquid chromatography–tandem mass spectrometry (HPLC-MS/MS), including caffeic acid, quercetin and catechol. Conclusion: Hawthorn leaf extract significantly alleviated the browning of fresh-cut potato. It could serve as a natural antibrowning alternative by stabilizing the membrane and modulating reactive oxygen species and redox reactions.